Geographic Distribution and Evaluation of Saccharomyces cerevisiae Strains Isolated from Vineyards in the Warmer, Inland Regions of the Western Cape in South Africa - Khan, W.; Augustyn, O.P.H.; van der Westhuizen, T.J.; Lambrechts, M.G.; Pretorius, I.S. (South African Journal of Enology and Viticulture, 2017)
The aim of this study was to examine the geographic distribution of Saccharomyces cerevisiae strains indigenous to 19 sites in the warmer, inland regions of the Western Cape in South Africa. These strains were compared to those isolated previously from the cooler, coastal regions of the same province by subjecting both sets of organisms to the same characterisation procedures. Thirty isolates per sampling site were isolated and the S. cerevisiae strains subjected to the following characterisation procedures; karyotyping using pulse field gel electrophoresis (CHEF), randomly amplified polymorphic DNA, the polymerase chain reaction technique (RAPD-PCR), sugar fermentation ability, flocculation ability, stress resistance/response and extracellular enzyme activity. When considering biodiversity per sampling site, CHEF karyotypes indicated the recovery of 30 S. cerevisiae strains. This number was reduced to 21 when comparing banding patterns over sites. Addition of RAPD-PCR data expanded the number of unique strains to 29. Subsequent consideration of sugar fermentation data indicated that one of the strians with exactly equivalent CHEF and RAPD-PCR patterns was in fact galactose positive while the other was galactose negative. These data clearly indicate that characterisation of yeast strains by application of a single technique is not a sound practice. None of the S. cerevisiae strains isolated in this study occurred in the coastal regions. In addition, each site sampled in this study had its own unique collection of wine yeast strains and no strain common to all sites in the study region was found. Survival mechanisms of S. cerevisiae are obscure. Although we found that many of the isolated strains could grow invasively/form pseudohyphae and that these abilities could therefore contribute to the organism’s overwintering ability, other mechanisms must also be involved.